Creating a sensory stimulation garden for older persons to cultivate happiness: a Hiroshima experience - Omar, Zaliha; Abu Hassan, Salmah Anim; Hussain, Hazreena; Amano, Junko (Elsevier, 2022)
Research Objectives: To design an age-friendly sensory stimulation gar-den (SSG) to cultivate happiness in older persons.Design: 12 nursing home residents were selected to provide video feed-back after a 30 minute, twice weekly exposure to six sections of the newlycreated SSG. A 60 second facial video and audio recording were taken atday 1, week 3 and week 6. The video recordings were translated from Japa-nese to English by a dedicated assistant and transcribed.Setting: We designed and built an SSG at an unused rooftop of Nozomi-No-Sato Nursing Home.With the sensory elements of hard and soft land-scaping, colours and textures, this garden encouraged users to touch, smell,and actively experience the garden with all their senses.Participants: 12 nursing home residents with an average age of 90.2 yearswere chosen subjects. Residents with moderate to severe dementia and bedridden condition were not selected.Interventions: The study subjects were given exposure to the SSG for 30minutes, twice weekly for six weeks.Main Outcome Measures: A 60 second facial video and audio recordingwere taken at day 1, week 3 and week 6. The recordings were translatedfrom Japanese to English by a dedicated assistant and transcribed.Results: Subjects’ reactions that were recorded during the garden exposureincluded negative and positive ones.The negative feedback was irritationfrom sun exposure. The positive ones included excitement about just beingout in the garden, recall of past experiences at Miyajima Island and garden-ing experiences before staying in the nursing home. At the times they werescheduled to be in the garden, they all expressed willingness and eagernessto do so. Some had made suggestions on what they would like to plantnext season. Six subjects wanted to participate in harvesting the productsof the garden.Conclusions: SSG exposure in older persons in nursing home fosteredfeeling of happiness. A study with a larger sample size is planned afterCOVID-19 restrictions are eased.